An update on multimodal imaging strategies for nipple discharge: from detection to decision - Mireia Pitarch; Rodrigo Alcantara; Laura Comerma; Ivonne Vázquez de Las Heras; Javier Azcona; Antonia Wiedemann; Maja Prutki; Eva Maria Fallenberg (Insights into Imaging)
Abstract Nipple discharge affects over 80% of women at some point in their lives, with malignancy detected in up to 23% of cases. This review highlights the shift from traditional surgical approaches to advanced imaging techniques, which enhance diagnostic accuracy and reduce unnecessary procedures. Diagnosis begins with a thorough medical history and physical examination to assess the need for imaging. Physiological nipple discharge, which is bilateral, multiductal, and non-spontaneous, typically requires no imaging. Conversely, pathological nipple discharge (PND), characteristically unilateral, uniductal, and spontaneous, requires imaging to rule out malignancy. Bloody PND is frequently associated with breast cancer, and up to 12% of non-bloody PND cases also involve malignancy. For women over 40 years, the first-line imaging modality is full-field digital mammography (FFDM) or digital breast tomosynthesis (DBT), usually combined with ultrasound (US). Men with PND undergo FFDM/DBT starting at age 25 years due to their higher risk of breast cancer. For women aged 30–39 years, US is the first assessment tool, with FFDM/DBT added, if necessary, while US is preferred for younger women and men. When initial imaging is negative or inconclusive, magnetic resonance imaging (MRI) is useful, often replacing galactography. With its high sensitivity and negative predictive value of almost 100%, a negative MRI can often obviate the need for surgery. Contrast-enhanced mammography (CEM) offers a viable alternative when MRI is not feasible. Although invasive, ductoscopy helps identify patients who may not require duct excision. This review consolidates the latest evidence and proposes an updated diagnostic algorithm for managing PND effectively. Critical relevance statement Effective management of nipple discharge requires recognising when imaging tests are needed and selecting the most appropriate diagnostic technique to rule out malignancy and avoid unnecessary interventions. Key Points First-line imaging for pathological nipple discharge (PND) assessment includes ultrasound and mammography. MRI is recommended for patients with PND and negative conventional imaging. A negative MRI is sufficient to justify surveillance rather than surgery. Contrast-enhanced mammography (CEM) is an alternative when MRI is unavailable or contraindicated. Graphical Abstract